Continuous monitoring of an ice sheet in a reservoir upstream of Beaumont dam, Canada - Santerre, Rock; Bourgon, Stéphanie; Prat, Yann; Morse, Brian; Desmet, Vincent (Journal of Surveying Engineering, 2016)
The geomatics engineering contributions to continuous three-dimensional monitoring of ice sheet in a dam reservoir is presented in this paper. A total station robot was used to monitor the displacement of several probes placed on the surface of the ice sheet of a dam reservoir during winter seasons. Two prisms were mounted on each probe to take into account the deflection variation of the probe during a complete winter season. A similarity (Helmert) transformation was computed from measurements on control points to solve the problem of inconsistent observations. The results of the 2009 and 2010 winter campaigns at the Beaumont Dam are reported in this paper. We show that the horizontal displacements of the ice sheet, which can be as large as 20-30 cm, can vary quite differently from one winter season to another one, as a function of the temperature and its variation during winter. The horizontal displacements also depend on the probe's distance from the dam or from the reservoir banks. Vertical displacements of the ice sheet follow the reservoir water level fluctuations, especially for the probes far from the dam and reservoir banks. Three-dimensional displacements are explained by the gradual increase of the ice sheet's thickness, the snowpack accumulation, and the local constraints (hinge effects) near the reservoir perimeter